2022
DOI: 10.1002/mde.3658
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of subsidy strategies and recycling modes on the closed‐loop supply chain

Abstract: This paper explored the effect of government subsidies and recycling modes on a four‐echelon closed‐loop supply chain (CLSC) including a government, a manufacturer, a retailer, and a third‐party recycler. The government directly subsidizes remanufacturing activities, recycling activities, or consumption activities with social welfare maximization objective. Meanwhile, the used products can be recycled by the retail, the third party, or both. We developed nine Stackelberg game models and derived the optimal dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Furthermore, the results demonstrate the possibility of vicious competition among recyclers. Thus, the government should launch relevant policies, such as subsidies, to ensure the sustainable development of the multichannel recycling market (Song et al, 2022). Stable development of different recyclers guarantees an increase in the total amount of recycled clothing.…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
“…Furthermore, the results demonstrate the possibility of vicious competition among recyclers. Thus, the government should launch relevant policies, such as subsidies, to ensure the sustainable development of the multichannel recycling market (Song et al, 2022). Stable development of different recyclers guarantees an increase in the total amount of recycled clothing.…”
Section: Numerical Experiments and Discussionmentioning
confidence: 99%
“…Cao et al (2020) compared the difference of CLSC production decisions under the government's remanufacturing subsidy policy and carbon tax policy and the impact of the two policies on society for the dual channel CLSC and pointed out that the remanufacturing subsidy policy is better suitable for curbing the carbon emissions of enterprises. Song et al (2022) studied the impact of government subsidy and recycling mode on the performance of CLSC and showed that the government directly subsidizes remanufacturing or recycling has the same effect. Hussain et al (2022) studied the government's green technology investment subsidy strategy for manufacturers based on the monopoly market of emission generation companies, helping the government find an optimal green technology investment and subsidy on green technology investment.…”
Section: Government Subsidy Strategies In Clscmentioning
confidence: 99%
“…But the above few studies investigated the impact of government subsidy strategies on the selection of CLSC recycling channels from the perspective of exogenous or endogenous government subsidies (Huang & Liang, 2021; Song et al, 2022). However, existing studies have not analyzed the impact of government subsidy strategies on manufacturer's online recycling channel intrusion decisions, nor have they considered the impact of digital technology empowerment on the selection of CLSC recycling modes and government subsidy strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations